2016
DOI: 10.1007/s13399-016-0227-5
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional aspects of biorefined Saccharina latissima, Ascophyllum nodosum and Palmaria palmata

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders. Please consult the full DRO polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 64 publications
3
16
0
2
Order By: Relevance
“…For example, Gévaert et al (2001) observed that for S. latissima in the English Channel, the maximum carbon content is reached in September with the lowest concentrations occurring in March. Similar trends have also been reported for Norway (Sjøtun, 1993) and Scotland (Connolly and Drew, 1985). The minimum carbon concentration in March occurs when the growth rate of the algae is high and the plant growth is carried out at the expense of carbohydrate reserves.…”
Section: Saccharina Latissimasupporting
confidence: 83%
See 2 more Smart Citations
“…For example, Gévaert et al (2001) observed that for S. latissima in the English Channel, the maximum carbon content is reached in September with the lowest concentrations occurring in March. Similar trends have also been reported for Norway (Sjøtun, 1993) and Scotland (Connolly and Drew, 1985). The minimum carbon concentration in March occurs when the growth rate of the algae is high and the plant growth is carried out at the expense of carbohydrate reserves.…”
Section: Saccharina Latissimasupporting
confidence: 83%
“…There has been increasing interest in the potential of macroalgae cultivation across the Northern Hemisphere and Europe (Van der Burg et al, 2016), partially driven by research on biofuel technologies (Kerrison et al, 2015). The characteristics of Phaeophyta macroalgae, in particular high productivity, fast growth rate and high polysaccharide content, make them a suitable biomass for biofuel production (Hughes et al, 2012;Kerrison et al, 2015;Schiener et al, 2017;Fernand et al, 2017). A further advantage is that such third-generation biofuels do not need additional freshwater and do not compete for agricultural land like many existing biofuel sources.…”
Section: Background Aims and Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos efectos de carácter tóxico pueden tener lugar debido a metabolitos del propio vegetal [35,37,43] o a especies químicas de origen antrópico que el organismo fotosintético absorbe durante su vida [48,51,52].…”
Section: Discussionunclassified
“…The characteristics of Phaeophyta macroalgae, in particular high productivity, fast growth rate and high polysaccharide content, make them a 10 suitable biomass for biofuels production (Hughes et al, 2012;Kerrison et al, 2015;Schiener et al, 2016;Fernand et al, 2017). A further advantage is that such third generation biofuels do not need additional freshwater and do not compete for agricultural land like many existing biofuel sources.…”
Section: Background Aims and Approachmentioning
confidence: 99%